The Effectiveness of a Training Program in Developing the Competencies of Special Education Teachers in Providing a Cognitively and Socially safe Learning Environment for Kindergarten Children With an Autism Spectrum Disorder in Jordan. - خزاعله, أحمد; الخطيب, عاكف; الشرمان, وائل; السريع, احسان (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The study aimed to determine the effectiveness of a training program in developing competencies related to a safe educational environment among members of the training group in the pre- and post-measurements. And determining priorities for improving the educational environment in kindergarten for children with integrated autism spectrum disorder in Jordan. The study sample consisted of (44) female special education teachers, to whom a questionnaire was applied to the competencies of the safe educational environment for special education teachers and the training program. The results of the current study showed that there were statistically significant differences at (α ≤ 0.05) attributed to the training program directed to special education teachers, in providing a safe educational environment in (the cognitive field, the emotional field, the social field, and the field of health and safety), and in favor of individuals in the training group. Those who were exposed to the program compared to the control group, which did not undergo training, noted that the effect size for the areas as a whole was high and ranged between 0.183 and 0.342. This means that the training program was effective in improving the level of educational competencies in all fields among the members of the experimental sample. The study concluded with several recommendations, most notably amending policies and practices related to inclusive programs in public schools for kindergarten children with autism spectrum disorder.